Psychological Perspectives on Risk and Risk Analysis Theory, Models, and Applications (Springer International Publishing, 2018)
This authoritative collection goes beyond economic statistics and probability data to offer a robust psychological understanding of risk perception and risk taking behavior. Expert contributors examine various risk domains in life, and pinpoint cognitive, emotional, and personality factors contributing to individual differences in risk taking as well as the many nuances social demographics (e.g., culture, gender) bring to risk decisions. Coverage takes competing theories and studies into account to identify mechanisms involved in processing and acting on uncertainty. And implications and applications are demonstrated in varied fields, from updated risk models for the insurance sector to improved risk communication in health services to considering risk perception in policy decisions. A sampling of the topics: Personality and risk: beyond daredevils-risk taking from a temperament perspective. Cognitive, developmental, and neurobiological aspects of risk judgments. The group effect: social influences on risk identification, analysis, and decision-making. Cognitive architectures as a scaffolding for risky choice models. Improving understanding of health-relevant numerical information. Risk culture as a framework for improving competence in risk management. Psychological Perspectives on Risk and Risk Analysis will be of great interest to researchers in and outside of psychology, including decision-making experts and behavioral economists. Additionally, this volume will appeal to practitioners who often have to make risky decisions, such as managers and physicians. Chapter 9 of this book is available open access under a CC BY 4.0 license at link.springer.com.